Cefepime MIC as a Predictor of the Extended-Spectrum β-Lactamase Type in Klebsiella pneumoniae, Taiwan - Wen Leong Yu; Michael A. Pfaller; Patricia L. Winokur; Ronald N. Jones (Emerging Infectious Diseases, 2002)
To guide selection of carbapenems or fourth-generation cephalosporins as therapy, 110 Klebsiella pneumoniae isolates with extended-spectrum β-lactamases from Taiwan were characterized by phenotypic (MICs), molecular, and chemical methods. MIC patterns of ceftazidime and cefepime clearly differentiate strains treatable by cefepime and those capable of efficiently hydrolyzing available cephalosporins (CTX-M series and SHV-types). Continued use of cefepime appears to be a treatment option in cases for which MIC results are available and interpreted by the criteria presented.